Clinical decision‐making and importance of the AAE/AAOMR position statement for CBCT examination in endodontic cases. (7th October 2020) - Bhatt, M.; Coil, J.; Chehroudi, B.; Esteves, A.; Aleksejuniene, J.; MacDonald, D.
Abstract: Aim: To compare conventional radiographic and cone beam computed tomography (CBCT) findings with reference to the American Association of Endodontics and American Academy of Oral and Maxillofacial Radiology (AAE/AAOMR) joint position statement and to determine the effect of the CBCT on the initial diagnoses and treatment plans in a single‐centre Postgraduate Endodontic Programme. Methodology: The clinical CBCT scans of patients, treated at the Endodontic Department of the University of British Columbia, were reviewed for CBCT referrals by comparing them with corresponding radiographs. The features considered were periapical lesions, missed/extra canals, root fractures, complex anatomy, calcified canals and root resorption of tooth/teeth in question. Reasons for the CBCT prescriptions were assigned to 3 groups: to formulate the primary diagnosis, to confirm the diagnosis achieved by clinical examination and conventional radiographs, and to assist in treatment planning. Variables were compared statistically using chi‐square and McNemar tests. Results: A total of 128 CBCT examinations were performed on 110 patients. No CBCT examination was performed more than once on the same tooth. Overall, 76% of CBCT examinations were performed on previously root filled teeth. CBCT images revealed a significantly higher incidence of periapical lesions ( P = 0.002), missed canals ( P < 0.001), vertical root fractures ( P = 0.004) and complex anatomy ( P = 0.008) than periapical radiographs. CBCT was prescribed most frequently to assist surgical treatment planning (62%) rather than for generating a diagnosis (9%) or confirming diagnoses (29%). Both the diagnosis ( P = 0.001) and the treatment plan ( P = 0.005) initially made by examining periapical radiographs were altered significantly by the subsequent CBCT examination by revealing information such as new periapical lesions, missed canals or involvement of buccal or lingual cortical bone. Conclusion: CBCT examinations were prescribed mainly to assist treatment planning rather than for diagnosis. The majority of CBCT examinations were performed on previously root filled teeth. The additional information obtained from CBCT scans resulted in the alteration of the initial diagnoses as well as subsequent treatment plans in 59 out of 128 cases.